2001
DOI: 10.1103/physrevb.63.073307
|View full text |Cite
|
Sign up to set email alerts
|

Charged and neutral exciton complexes in individual self-assembledIn(Ga)Asquantum dots

Abstract: Charged (X*) and neutral ͑X͒ exciton recombination is reported in the photoluminescence spectra of single In͑Ga͒As quantum dots. Photoluminescence excitation ͑PLE͒ spectra show that the charged excitons are created only for excitation in the barrier or cladding layers of the structure, consistent with their charged character, whereas the neutral excitons in addition show well-defined excitation features for resonant excitation of the dots. The PLE spectra for X and X* exhibit a clear anticorrelation in the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
3
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(97 citation statements)
references
References 22 publications
10
83
3
1
Order By: Relevance
“…Using this method, splittings below the resolution of the spectrometer can be determined, and a value of ¡ AES = 200 µeV is obtained for this particular dot. PL from single dots typically contain multiple emission lines corresponding to recombination of excitons with more than one charge state [56]. This is highlighted in Fig.…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…Using this method, splittings below the resolution of the spectrometer can be determined, and a value of ¡ AES = 200 µeV is obtained for this particular dot. PL from single dots typically contain multiple emission lines corresponding to recombination of excitons with more than one charge state [56]. This is highlighted in Fig.…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…There is striking difference between two charged exciton species, i.e., the X − line was almost quenched below about 85 meV from the detection energy, while the X + survived at lower energy and much richer structures tentatively attributed to phonon resonances and excitation states [15][16][17][18] were observed. For delocalized state excitation, since the absorption coefficient is identical for both the neutral and charged trions, carrier capture process will determine the exciton charging states [11,12]. In most of the QDs examined, the X + and X 0 were commonly observed, whereas the X − line was less available.…”
Section: Resultsmentioning
confidence: 99%
“…Resultant DCP amounts to ~0.6, which indicates that mutual polarization conversion between single photon and single electron spin is realized with high efficiency. Control of the exciton charging state dominating the spectrum is also discussed via excitation energy tuning, as reported for neutral excitons [11,12].…”
Section: Figmentioning
confidence: 99%
“…Note that a PL peak is located on the lowenergy tails of the half-localized states, as shown in the PLE spectra. Previous studies [13][14][15][16][17] suggested that these continuumlike tails were due to transitions between one of the carriers in a QD and the other carrier in the wetting layer, which is a quantum well with about 1 ML thickness beneath the QD.…”
Section: Methodsmentioning
confidence: 99%
“…Even in a QD, the observed nuclear spin polarization is small when electron-hole pairs are optically created with an excitation light having the barrier band gap energy. 7 On the other hand, when electron ͑hole͒ spin is generated in "half-localized" states [13][14][15][16][17] that consist of electron and hole states, one of which is confined to the ground state of the QD, the observed Overhauser field is of a few tesla, 8 because one of the carriers ͑possibly an electron͒ confined in a QD preserves the spin state with high possibility. 18 The half-localized states are significantly important to understand the practical QD physics.…”
Section: Introductionmentioning
confidence: 99%